2023
DOI: 10.1097/hjh.0000000000003414
|View full text |Cite
|
Sign up to set email alerts
|

Association of hydrochlorothiazide treatment compared with alternative diuretics with overall and skin cancer risk: a propensity-matched cohort study

Abstract: Introduction:Hydrochlorothiazide (HCT) has been suggested to induce photosensitivity, thereby increasing the incidence of skin cancers. After a pharmacovigilance alert, HCT was frequently withdrawn or substituted by other diuretics. The aim of this study was to compare the association of exposure to HCT with cancer risk versus alternative diuretics.Methods:A retrospective cohort study was conducted based on data from the AOK PLUS, a large German statutory health insurance fund. Patients with HCT treatment were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…However, the increased risk was seen only in women, and no biological rationale was offered for this finding [687]. Finally, a large propensity-matched cohort study in Germany found that hydrochlorothiazide was associated with not only a small increase of skin cancer risk but also with an overall lower risk for any cancer compared with other diuretics [688]. Further well designed observational studies are needed to provide a more solid evidence on the association between hydrochlorothiazide and skin cancer risk.…”
Section: Antihypertensive Drugs and Cancer Riskmentioning
confidence: 99%
“…However, the increased risk was seen only in women, and no biological rationale was offered for this finding [687]. Finally, a large propensity-matched cohort study in Germany found that hydrochlorothiazide was associated with not only a small increase of skin cancer risk but also with an overall lower risk for any cancer compared with other diuretics [688]. Further well designed observational studies are needed to provide a more solid evidence on the association between hydrochlorothiazide and skin cancer risk.…”
Section: Antihypertensive Drugs and Cancer Riskmentioning
confidence: 99%
“…Although both commonly known and used drugs such as HCT and FUR are initially subjected to phototoxicity test, many new reports, systematic reviews, and cohort studies of phototoxic reactions have been reported as an adverse effects of pharmacotherapy with these drugs [14,[27][28][29]. Moreover, a lot of recent pharmacoepidemiological data have appeared to link a dose-dependent, cumulative association between long-term HCT treatment and increased risk of skin cancer [24,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Although both commonly known and used drugs such as HCT and FUR are initially subjected to phototoxicity test, many new reports, systematic reviews, and cohort studies of phototoxic reactions have been reported as an adverse effects of pharmacotherapy with these drugs [14,[27][28][29]. Moreover, a lot of recent pharmacoepidemiological data have appeared to link a dose-dependent, cumulative association between long-term HCT treatment and increased risk of skin cancer [24,[27][28][29]. The meta-analyses of the relationship between pharmacotherapy with thiazide diuretics and the risk of skin cancer demonstrated an increased risk of developing non-melanoma skin cancers-squamous cell carcinoma (SCC) and basal cell carcinoma (BCC), for which the OR value was 1.86 and 1.19, respectively, and melanoma cancer (OR 1.14) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Propensity Score Matching) erfolgte. Nach dem Abschluss der Auswertung ergab sich auch hier ein leicht erhöhtes Hautkrebsrisiko von 0,05 Hautkrebsdiagnosen mehr auf 100 Patientenjahre für die HCT-Gruppe, demgegenüber steht jedoch die signifikant niedrigere Inzidenzrate für alle Krebsarten in der HCT-Gruppe [18]. Dies deckt sich auch mit einer Metaanalyse aus dem Jahr 2021, in der kein Zusammenhang zwischen einem Antihypertensivum im Allgemeinen und einem erhöhten Krebsrisiko identifiziert werden konnte [19].…”
Section: Thiazid-und Thiazidartige Diuretikaunclassified